1992
DOI: 10.1259/0007-1285-65-773-451
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of an oesophageal stricture due to lichen planus

Abstract: Involvement of the oral mucous membranes occurs commonly in lichen planus. Oesophageal involvement is less common and may result in pain, dysphagia and strictures. We present a case of an oesophageal stricture in a patient with lichen planus. A 44-year-old woman with a 24 year history of oral lichen planus and a 9 year history of anogenital involvement gave a 2 year history of dysphagia. An endoscopy performed when she first noticed dysphagia showed oropharyngeal ulceration and the pharynx was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…All of our patients had oral and mucous membrane disease, however, their oral lesions did not flare after esophageal dilation. In contrast with oral lichen planus, no known progression of esophageal lichen planus to esophageal malignancy has been described 12 . One author suggested that surveillance of the esophagus for development of squamous cell carcinoma may be indicated 13 …”
Section: Clinical and Endoscopic Findingsmentioning
confidence: 99%
See 3 more Smart Citations
“…All of our patients had oral and mucous membrane disease, however, their oral lesions did not flare after esophageal dilation. In contrast with oral lichen planus, no known progression of esophageal lichen planus to esophageal malignancy has been described 12 . One author suggested that surveillance of the esophagus for development of squamous cell carcinoma may be indicated 13 …”
Section: Clinical and Endoscopic Findingsmentioning
confidence: 99%
“…Dilation is commonly used despite concerns about worsening esophageal stenosis or oral lesions due to Koebner phenomenon. Other regimens described include adrenocorticotropic hormone injections, oral corticosteroids, etretinate, and topical corticosteroids 1,11–23 . Topical tacrolimus, a potent inactivator of T‐lymphocytes used initially in patients with transplants, was successful for oral lichen planus in six patients 24–26 Table 3.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Oesophageal involvement in lichen planus is very rare, only 17 cases [7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22]and a series of 6 patients in 15 years from the Mayo Clinic [23]have been reported in the literature so far. This complication is probably underestimated, since a small study in 1990 on 19 patients with OLP demonstrated that a quarter of those had oesophageal involvement [24](table 1).…”
Section: Introductionmentioning
confidence: 99%